The Influence of Lifestyle and Social Groups on Purchase Decisions with Trend as Moderating Variables - Maya Citra (PT Inovasi Pratama Internasional, 2022)
This study aims to determine the effect of lifestyle and social groups on purchasing decisions with Trend as a moderating variable. This research is a quantitative research. The sampling technique used was the saturated sampling method and the non-probability sampling technique with the criteria of high school motorcycle customers who would be the research sample. The data analysis technique used is validation test, reliability test, classical assumption test, multiple linear regression test , coefficient of determination, hypothesis testing and interaction test (MRA). The results showed that lifestyle had a positive effect on purchasing decisions with a tcount of (0.3259) > ttable of (0.2787), with a significant value of 0.02 <0.05. And the results of social group variables do not have a positive effect on purchasing decisions, with a tcount of (0.834) < ttable of (0.2787) and a significance value of 0.409 > 0.05. This study uses the moderating variable with the interaction method (MRA) to obtain the results that Trend is not able to moderate the influence of lifestyle on purchasing decisions with a significant value of interaction variable between lifestyles 0.128> 0.05 which means Trend is not able to moderate lifestyle on purchasing decisions. And Trend is not able to moderate social groups on purchasing decisions with a significant value of social group variables of 0.237 > 0.05, which means that Trend variables are not able to moderate social group variables on purchasing decisions.